“Difficult diabetes” – essence of disease or healthy behavior? - Krzymień, Janusz (Przewodnik Lekarza/Guide for GPs, 2006)
Some of the patients with diabetes suffer chronically poor diabetic control. These patients cannot be controlled adequately, even by closed supervised, intensive insulin regimens. Obesity, puberty (due mainly to increased growth-hormone secretion) infections, endocrine hypersecretion, many used drugs may be responsible for metabolic instability. Reccurent hypoglycemia is common in patients with impaired awareness of hypoglycemic warning symptoms. Many patients with recurent hypoglycemia have psychiatric and psychological problems. Mental health problems occur frequently in diabetes, depression is the commonest disorder, but it is often unrecognized and untreated. Diabetic subjects with eating disorders, patients ommiting or decreasing the insulin dose to control weight generally have poor metabolic control. A psychologist or other mental health-care professional should be part of the diabetes care team.